Organization of the musical church collection of the Church among the Palms - Rasco, Mary Ruth O.; Olgado, Benedict S.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2018)
The project involved the organization of the musical score collection of the Church Among the Palms through accessioning, indexing, filing and storage of the musical scores in steel cabinets for easy access and retrieval. The procedures were made easy and practical so that non-librarians can also be given the task to ensure continued organization of the collection. A total of six hundred (600) musical score titles and twenty four (24) songbook titles were accessioned, indexed, and filed.
Rules and regulations for the use of the collection were also drafted to guide and inform users about their responsibilities in the upkeep and maintenance of the collection. Digitization of some musical score titles has already been initiated and about sixty (60) musical score titles have already been digitized to provide alternative access to the collection and for backup purposes in case unforeseen disaster occurs.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Musical score -- Collection